Effect of porous polysulfone membrane’s thickness on flux of ferum ions: article - Mohamed Zaimy, Nabilla; Kassim Shaari, Norin Zamiah; Sulaiman, Nurul Aida (2017)
Membrane separation has been widely used in removal of heavy metal from wastewater. In this research, the wastewater from electroplating industry that contains high concentration of ferum ion was treated by using integrated complexation method through a thin film composite membrane. Chemical precipitation, ion exchange and adsorption are the example of conventional treatment that have significant disadvantages which are incomplete removal, need high energy and result in toxic sludge.